The Role of Customary Law in Family Resilience and Divorce Prevention: Phenomenological Studies in Indonesia - Usman, Munadi; Abdullah, Abdullah; Kafrawi, Kafrawi; Jafar, Muhammad (Institut Agama Islam Negeri Curup, 2024)
Based on data released by the Central Statistics Agency, the divorce rate in Indonesia continues to increase every year due to various factors behind it. The rise of divorce and the fragility of family resilience is partly due to the ineffectiveness of customary law in preventing this. So this research was conducted to examine the existence of customary law in creating family resilience and preventing divorce. This type of research is descriptive-qualitative with a phenomenological approach. Data collection was carried out through focus group discussions (FGD) with traditional leaders about customary rules that are applied to create family resilience and prevent divorce. The research results show that traditional institutions have made customary regulations to create family resilience and prevent divorce, including making customary rules to minimize divorce, requiring prospective brides and grooms to take pre-marital courses, resolving husband and wife conflicts and preserving marriage traditions. However, the application of customary law in creating family resilience and preventing divorce faces a number of internal and external challenges. Internally, the obstacles include weak competence of traditional leaders in carrying out their functions as executors of customary law, decreased public trust in traditional leaders, and decreased public awareness of implementing customary law in marriage processions. External challenges include government policies that amputate the role of customary law in society, and the lack of government support for customary institutions. So the role of customary law needs to be revitalized as local wisdom which really functions to solve various problems in society.